Literature Review: Pengaruh Daun Seledri terhadap Penurunan Tekanan Darah pada Lansia dengan Hipertensi - Herliani, Lita Dwi; Krishna, Lucia Firsty Puspita (Maternal & Neonatal Health Journal, 2025)
Hypertension is one of the most common degenerative diseases experienced by the elderly and can cause serious complications if left unattended. One alternative to non-pharmacological therapy used is the use of herbs, such as celery leaves. Celery leaves contain active compounds such as apigenins and phthalides that have diuretic effects and vasodilators. To determine the effectiveness of celery leaf boiled water in lowering blood pressure in the elderly through review literature. This study used a literature review method of five articles obtained through a systematic search using Google Scholar with certain inclusion and exclusion criteria. Studies show that the administration of celery leaf stew is effective in significantly lowering systolic and diastolic blood pressure. A celery leaf stew is effective as a nonpharmacological therapy to lower blood pressure in the elderly with hypertension.